The Basic Psychological Need Satisfaction and Frustration Scale in Exercise (BPNSFS-E): Validity, Reliability, and Gender Invariance in Portuguese Exercisers. Issue 5 (October 2019) - Rodrigues, Filipe; Hair, Joseph F.; Neiva, Henrique P.; Teixeira, Diogo S.; Cid, Luís; Monteiro, Diogo
The aim of this study was to translate and validate the Basic Psychological Need Satisfaction and Frustration Scale for Portuguese exercisers. In addition, we sought to analyze gender invariance. We collected data from two independent samples of Portuguese respondents—a calibration sample with 316 participants and a validation sample with 632 participants. Results from confirmatory factor analysis supported the original six-factor model in both the calibration sample, χ 2 (237) = 471.814, χ 2 / df = 1.99; B–S p < .001, Comparative Fit Index = .935, Tucker–Lewis Index =.924, standard mean root square residual = .047, root mean square error of approximation = .057 (90% confidence interval = [.050, .065]), and the validation sample, χ 2 (237) = 571.796, χ 2 / df = 2.41; B–S p < .001, Comparative Fit Index = .948, Tucker–Lewis Index = .940, standard mean root square residual = .038, root mean square error of approximation = .047 (90% confidence interval = [.042, .052]). Moreover, our analysis revealed acceptable internal consistency, convergent and discriminant validity of the translated version, and invariance between the two samples and between genders, as differences across latent means showed that magnitude effects were trivial between samples and between male and female exercisers. These results support the use of the adapted scale among both male and female exercisers.